1997
DOI: 10.1038/sj.ijo.0800391
|View full text |Cite
|
Sign up to set email alerts
|

β3-adrenergic-receptor allele distributions in children, adolescents and young adults with obesity, underweight or anorexia nervosa

Abstract: OBJECTIVE: The missense mutation (64Trp to 64Arg) in the b 3 -adrenergic-receptor has previously been described to confer a genetic predisposition to the development of obesity. DESIGN: To test the hypothesis we evaluated allele frequencies in children, adolescents and young adults who belonged to different weight groups that were delineated with percentiles for the body mass index (BMI; kg/m 2 ). SUBJECTS: 99 underweight probands (BMI 15th percentile). 80 normal weight probands (BMI: 5th±85th percentile). 238… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
40
0
2

Year Published

1998
1998
2008
2008

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 78 publications
(49 citation statements)
references
References 18 publications
7
40
0
2
Order By: Relevance
“…These results are consistent with those of the main meta-analysis. From the weighted regression analysis, neither the linear nor the quadratic effect of the 3,8,11,12,21); N: non-diabetics (ID; 2,5,7,13,14,19,20,22,23,26,30,31); CaU: combinedaUnknown (ID; 1,4,6,9,10,15,16,17,18,24,25,27,28,29,32,33,34,35,36).…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…These results are consistent with those of the main meta-analysis. From the weighted regression analysis, neither the linear nor the quadratic effect of the 3,8,11,12,21); N: non-diabetics (ID; 2,5,7,13,14,19,20,22,23,26,30,31); CaU: combinedaUnknown (ID; 1,4,6,9,10,15,16,17,18,24,25,27,28,29,32,33,34,35,36).…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…3,4 Their allelic frequencies range from 0.08 to 0.25 for the polymorphism Pro12Ala of the PPARg2 gene and from 0.05 to 0.19 for Trp64Arg variant of the ADRb3 gene in Caucasian populations. [5][6][7][8][9][10] Interestingly, Hsueh et al 11 found a gene  gene interaction on obesity between variants of ADRb3 (Trp64Arg) and PPARg2 (Pro12Ala) in Mexican-American adults. They reported that these two polymorphisms accounted for 2-3% of the total variation in BMI, serum insulin and leptin, with the interaction accounting for about half of their total effect.…”
Section: Introductionmentioning
confidence: 99%
“…Data from Germany have failed to show association with a number of candidate loci. [1][2][3] However, the list of genes that might theoretically play a role in this disorder is far from exhausted.…”
mentioning
confidence: 99%